Familial juvenile hyperuricemic nephropathy as rare cause of dialysis-dependent chronic kidney disease—a series of cases in two families. (25th November 2016) - Kaminska-Pajak, Kamila A.; Dyga, Katarzyna; Adamczyk, Piotr; Szczepańska, Maria; Zaniew, Marcin; Beck, Bodo; Tkaczyk, Marcin
Abstract: Hyperuricemia is a common symptom in adult population. It usually accompanies the chronic kidney disease. Less frequently, it is a primary phenomenon causing later serious clinical consequences. Familial juvenile hyperuricemic nephropathy (FJHN) is one of the hereditary conditions associated with high levels of serum uric acid and leading to dialysis in young adult age. It results from mutation in the UMOD gene, encoding the uromodulin protein, that is, Tamm–Horsfall protein. The aim of this paper was to present two families (7 affected members) with FJHN, in whom standard nephrological diagnostics did not provide clear cause of dialysis-dependent chronic kidney disease, until genetic testing was performed.